Peranan Subak dalam Aktivitas Pertanian Padi Sawah (Kasus di Subak Dalem, Kecamatan Kerambitan, Kabupaten Tabanan) - ARYAWAN, I PUTU SONY; WINDIA, WAYAN; WIJAYANTI, PUTU UDAYANI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2013)
Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:12.0pt; mso-para-margin-left:0cm; text-align:justify; line-height:150%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} ABSTRACT Subak Role in Agricultural Activities Rice Rice Fields Subak as an organization that regulates the distribution of water in the rice is one of Bali's cultural heritage that has been recognized worldwide. Where existence is in dangered due to start behavioral changes manners subak.The purpose of this study was to determine the role of subak in rice farming activity seen from the five subak role. The approach taken in this study with descriptive qualitative method by conducting in-depth interviews about the problems facing subak seen from the five subak role in rice farming activities. The results showed the role of subak in rice farming activities begin reduced. If this is going to endanger the continued existence of subak. There fore, it needs to be more participation of farmers to assist in ferforming subak rice farming activities. Subak role in the distribution and operation of Dalem Subak irrigation water , there is a problem due to lack of attention to soil conditions that cause distriubusi Dalem Subak irrigation water is not adequate for the needs of area farmers' fields . Subak role in the operation and maintenance of irrigation networks , the results of in-depth interviews with key informants . Irrigation channel in Subak Dalem still often blocked due to garbage thrown into . Keywords: Subak’s role, rice farming, existence of subak